(untitled) - Spring, Joel H. (Boston, Mass., 2006)
This book is to provide an understanding of the political, social, and economic forces shaping the direction of American education.
Keywords: Education,Education,Educational equalization,Giáo dục; Social aspects,Political aspects,Khía cạnh xã hội; United States,United States,United States